Dendrobium officinale Polysaccharide Protected CCl4-Induced Liver Fibrosis Through Intestinal Homeostasis and the LPS-TLR4-NF-κB Signaling Pathway - Kaiping Wang; Xiawen Yang; Zhijing Wu; Hongjing Wang; Qiang Li; Hao Mei; Ruxu You; Yu Zhang (Frontiers Media S.A., 2020)
We explored the therapeutic effects of Dendrobium officinale polysaccharide (DOP) on CCl4-induced liver fibrosis with respect to the intestinal hepatic axis using a rat model. Histopathological staining results showed that DOP alleviated extensive fibrous tissue proliferation in interstitium and lessened intestinal mucosal damage. Western blot and PCR results showed that DOP maintained intestinal balance by upregulating the expression of tight junction proteins such as occludin, claudin-1, ZO-1, and Bcl-2 proteins while downregulating the expression of Bax and caspase-3 proteins in the intestine. The transepithelial electrical resistance (TEER) value of the LPS-induced Caco-2 monolayer cell model was increased after DOP administration. These illustrated that DOP can protect the intestinal mucosal barrier function. DOP also inhibited activation of the LPS-TLR4-NF-κB signaling pathway to reduce the contents of inflammatory factors TGF-β and TNF-α, increased the expression of anti-inflammatory factor IL-10, and significantly decreased α-SMA and collagen I expression. These results indicated that DOP maintained intestinal homeostasis by enhancing tight junctions between intestinal cells and reducing apoptosis, thereby inhibiting activation of the LPS-TLR4-NF-κB signaling pathway to protect against liver fibrosis.